Thanatophoric Dysplasia - Basyir, Vaulinne; Yusrawati, Yusrawati; Khatimah, Gistin Husnul (Fakultas Kedokteran Universitas Andalas, 2021)
Background: The term tanatophorik comes from the Greek word thanatophorus which means